THE NECESSITY OF IMPROVING THE PRACTICE OF LENDING TO INDUSTRIAL ENTERPRISES BASED ON INNOVATIONS (Eureka Journal of Business, Economics & Innovation Studies, 2025)
The development of industrial enterprises significantly depends on the availability of financial resources. Innovative approaches in crediting play a crucial role in enhancing production efficiency and competitiveness. Modern credit systems face challenges such as high interest rates, limited access for small and medium enterprises, and slow adaptation to technological innovations. Integrating digital technologies, fintech solutions, and risk assessment models can improve credit allocation and reduce financial risks. This study analyzes current credit practices, identifies barriers, and proposes innovative strategies to optimize lending processes. Emphasis is placed on increasing transparency, fostering collaboration between banks and enterprises, and promoting sustainable investments.